2020
DOI: 10.1177/2047487320914756
|View full text |Cite
|
Sign up to set email alerts
|

HDL-C is associated with mortality from all causes, cardiovascular disease and cancer in a J-shaped dose-response fashion: a pooled analysis of 37 prospective cohort studies

Abstract: Objective The association between high-density lipoprotein cholesterol (HDL-C) levels and mortality remains controversial. We aimed to investigate the potential dose–response associations between HDL-C levels and mortality from all causes, cardiovascular disease and cancer in the general population. Methods PubMed and Embase were searched through April 2019. Prospective cohort studies reporting risk estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 75 publications
(232 reference statements)
4
67
1
Order By: Relevance
“…The study indicated that both the lowest and highest HDL-C levels were related to increased all-cause and cardiovascular mortality risk. 15 Similarly, Sun et al found that, in the general Chinese adults, the relation of HDL-C and allcause mortality was U-shaped and that HDL-C≥80 mg/dl was significantly correlated with greater risk of all-cause death. 20 Another study using data from the NHANES 1999-2010 showed that extremely high (≥100 mg/dL) or low (<30 mg/dL) levels increased risk of all-cause deaths and deaths from coronary heart disease and stroke in American adults, but the results were not stratified by hypertension status.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The study indicated that both the lowest and highest HDL-C levels were related to increased all-cause and cardiovascular mortality risk. 15 Similarly, Sun et al found that, in the general Chinese adults, the relation of HDL-C and allcause mortality was U-shaped and that HDL-C≥80 mg/dl was significantly correlated with greater risk of all-cause death. 20 Another study using data from the NHANES 1999-2010 showed that extremely high (≥100 mg/dL) or low (<30 mg/dL) levels increased risk of all-cause deaths and deaths from coronary heart disease and stroke in American adults, but the results were not stratified by hypertension status.…”
Section: Discussionmentioning
confidence: 95%
“…For example, a J-shaped or U-shaped association between HDL-C and allcause mortality or cardiovascular mortality was observed in the general population. [15][16][17][18][19] In addition, a cohort study from China found that both lower and higher HDL-C were associated with increased risk of CVDs in the general rural China population, but results for cardiovascular mortality were not significant. 20 In patients with type 2 diabetes, participants with relatively high HDL-C concentration had higher risk of CVDs and all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Zhong et al reported that both high and low HDL-C levels (ranging from 22 mg/dL to 97 mg/ dL) were associated with an increased risk of mortality from CAD [38]. The lncRNAs identified in this study provide insights into the potential molecular mechanisms underlying the effects of low HDL-C levels.…”
Section: Discussionmentioning
confidence: 70%
“…There are several studies investing the relationship between HDL-C and mortality conducted among general population in recent years ,most of which revealed J-shaped or U-shaped relationship (3-5, 22, 23). For example, Zhong et al (3)'s research demonstrated that in the general population, HDL-C level is associated with all-cause mortality in a J-shaped dose-response manner with the lowest risk observed at HDL-C levels of 54-58 mg/dL ; both extremely high and low HDL-C levels are associated with an increased risk of mortality. Mazidi et al(4) reported both extremely low(≤ 30 mg/dL) and extremely high(≥ 100 mg/dL) HDL-C levels were associated with greater risk of mortalities among American adults.…”
Section: Discussionmentioning
confidence: 99%